Political Biography of Raden Usman Dung: The Dedication of an Ulama in Muara Bungo Tebo, Jambi - Aura miftah; Siti Syuhada; Zulfa Saumia (Journal of Islamic History and Manuscript, 2024)
This research aims to find out Usman Dung. Biography of Usman Dung: Family, Career, Religion, Politics. The problem raised in this research is Usman Dung's Biography: Family, Career, Religion, Politics, which includes Usman Dung's family background, Usman Dung's figure, as well as Usman Dung's career in the religious and political fields. The author uses historical methods. In this method there are four stages including heuristics, source criticism, interpretation, and historical writing. To make writing easier, the author uses social role theory and biographical theory. The results of this research are that Usman Dung comes from a family that is able to support him in terms of freedom in continuing his education, he also builds his own family accompanied by a wife who also supports his work by not forgetting to educate his children, in the course of Usman Dung's religious and political career. has gone through many various positions and positions, of course based on the religious knowledge he has, with many career paths starting from being an Educator at a Madrasah then becoming Chairman of the MUI (Indonesian Ulema Council) Bungo - Tebo, and becoming Deputy Chairman of the DPRD-GR (Regional People's Representative Council – Mutual Cooperation) Bungo-Tebo, until he became a Member of the DPRD (Regional People's Representative Council) Bungo Tebo for two terms.